Istilah-Istilah dalam Ritual Kadeso di Dusun Jimbaran, Kabupaten Semarang (Kajian Antropolinguistik) - Rismawati, Rismawati; Suyanto, Suyanto; Tiani, Riris (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2023)
The Kadeso Ritual is a traditional ceremony performed by the people of Jimbaran Hamlet, Bandungan District, Semarang Regency every two years, Jumat Pon, Bakda Mulud. Kadeso rituals contain specific terms, including activities/processions, offerings, and equipment that are interesting to study. This study aims to describe the cultural meaning and cultural values contained in the terms of the Kadeso ritual. The theory used is anthropolinguistics and cultural values. Methods of data collection by observation and interviews. Observations were made by going directly to the Kadeso ritual. Meanwhile, the interviews were conducted using basic fishing techniques, followed by all-talking techniques, as well as recording techniques and note-taking techniques. The method of data analysis was carried out in an ethnographic descriptive. Presenting the results of data analysis formally and informally. The results of the study revealed that the Kadeso ritual consisted of three stages, namely pre-procession, implementation of the procession, and post-procession. Overall, there are 43 terms in the ritual. The cultural meaning describes the terms of the Kadeso ritual in three anthropolinguistic concepts, namely: performance, indexicality, and participation. Cultural values produce five components, namely the value of human relations with God, humans and nature, human relations with society, human relations with other human beings, and human relations with themselves. Dusun Jimbaran expresses their mindset and hopes through every term used in the Kadeso ritual.